Diversity of Freshwater Calanoid Copepods (Crustacea: Copepoda: Calanoida) in Southern Vietnam with an Updated Checklist for the Country - Phuttaphannee Boonmak; Laorsri Sanoamuang (Diversity, 2022)
The diversity of freshwater calanoid copepods from different habitats in Vietnam is investigated based on our findings from a field expedition in 2012–2013 and literature reviews. We collected 160 samples from 87 sites, including lakes, ponds, roadside canals, rivers, and rice fields in eight provinces of southern Vietnam. A total of 13 species belonging to eight genera and three families were recorded. Among these, four were recorded for the first time in Vietnam (Mongolodiaptomus malaindosinensis, Mongolodiaptomus mekongensis, Vietodiaptomus blachei, and Pseudodiaptomus siamensis). One unidentified taxon (Tropodiaptomus sp.) probably belongs to an undescribed species. Both Eodiaptomusdraconisignivomi and M. malaindosinensis were the most frequently encountered species (28.74% of the sampled sites), followed by Mongolodiaptomus botulifer (24.14%), while Neodiaptomus yangtsekiangensis, Tropodiaptomusoryzanus, and Tropodiaptomus sp. are rare species found in a single locality. To date, 40 calanoid species (33 in the family Diaptomidae) have been recorded from Vietnam, and an updated list is presented. Seven species are potentially endemic to Vietnam. At the same sampling dates, the species richness of the calanoids was a range of 1–5 species per locality. The results of the Canonical Correspondence Analysis showed that pH and conductivity tended to be positively related to the calanoid distribution.